14=-2(3-m)

Simple and best practice solution for 14=-2(3-m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14=-2(3-m) equation:


Simplifying
14 = -2(3 + -1m)
14 = (3 * -2 + -1m * -2)
14 = (-6 + 2m)

Solving
14 = -6 + 2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2m' to each side of the equation.
14 + -2m = -6 + 2m + -2m

Combine like terms: 2m + -2m = 0
14 + -2m = -6 + 0
14 + -2m = -6

Add '-14' to each side of the equation.
14 + -14 + -2m = -6 + -14

Combine like terms: 14 + -14 = 0
0 + -2m = -6 + -14
-2m = -6 + -14

Combine like terms: -6 + -14 = -20
-2m = -20

Divide each side by '-2'.
m = 10

Simplifying
m = 10

See similar equations:

| 4x-1x(9-3x)=8x-1 | | 2/5x3/4= | | 7x-7x=3 | | 2n+1=63 | | 2a+10=2 | | 8(x-18)=272 | | 3d+15=21 | | 6a+9-(-12a+24)=15 | | x+4-9+4x-9=180 | | .069x+x=59 | | -3(x-4)=12-3x | | 42-12t=30 | | 2x-5x=5-9 | | (2x/3)-(4x/5) | | (x+4)2=(4-x)(4+x) | | 2x/3-4x/5 | | 8(x+1)=8x+1 | | 11-3k=-4(1+2k) | | xa=d | | 56=-1+3x | | 7(2a-8)+6=-92 | | 5-9a-14/3(2a) | | Z=-5z | | 2x^3-4x^2= | | 2l+6=6-10 | | Y-2+3x=6+5x | | 1/2x-y=3 | | 4x-(2x-10)=2x-6 | | sqrtx+2=3 | | 12x+10=14x | | -5(3-q)+4=5q | | 5(b+1)-6=2b-16 |

Equations solver categories